Detection of transmissible gastroenteritis virus using cDNA probes - Benfield, D. A. (Arch Virol, 1991)
Five cDNA probes prepared from molecular clones representing genomic RNA sequences of the virulent Miller strain of transmissible gastroenteritis virus (TGEV) were used in a dot blot hybridization assay to detect TGEV in cell culture and fecal specimens. Two clones (pA2 and pB4) represent nucleotide base pairs at the 3′ terminus of the Miller TGEV genome. The other three clones represent various portions of the 5′ end of the E 2 gene, which codes for the major surface glycoprotein of TGEV. Each of the(32)P-labeled cDNA probes hybridized to the virulent Miller, attenuated Purdue and four field strains of TGEV. The probes detected 200 to 2000 pg of TGEV RNA extracted from density gradient purified virions and did not hybridize RNA from mock-infected cell cultures, porcine rotavirus or antigenically unrelated coronaviruses. The pB4 and Hpa-1600 probes detected TGEV RNA sequences in 79 and 88%, respectively of 34 field samples identified as TGEV positive by the immunofluorescence assay and electron microscopy (EM). The pD24 clone, which is able to differentiate TGEV from the antigenically related coronaviruses, also compared favorably with conventional methods of EM and immunofluorescence for the detection of TGEV in fecal specimens.